Ecological risk assessment for tris(2-chloroethyl) phosphate to freshwater organisms - Qiao, Yu; Liu, Daqing; Feng, Chenglian; Liu, Na; Wang, Jindong; Yan, Zhenfei; Bai, Yingchen (Frontiers in Environmental Science, 2022)
With the ban of brominated flame retardants (BFRs), organophosphate flame retardants (OPFRs) were used as the substitute generally as flames retardants, lubricants, plasticizers and so on. Tris(2-chloroethyl) phosphate (TCEP) is a common OPFR and has been widely detected in different environmental compartments such as atmosphere, dust, water, sediment and soil. At elevated levels, TCEP can cause adverse health effects on humans and aquatic life. The present study aimed to use bibliometrics analysis the important researches about TCEP and assess the risk of TCEP to aquatic life through a comprehensive meta-data analysis on available secondary data on its toxic effects and exposure levels. The results showed that toxicity and environmental occurrence and concentration are research hot spot. Meanwhile, given the relatively high detection rates and high concentrations of TCEP in some freshwaters, the ecological risk of TCEP to freshwater organisms should not be ignored. This result of the present study could provide data supports and references for the risk assessment and environmental management for such new emerging contaminants.